ARAHAN KEBIJAKAN PENGENDALIAN EROSI DAN SEDIMENTASI DI SUB DAERAH ALIRAN SUNGAI KEDUANG KABUPATEN WONOGIRI - Joko Sutrisno; Bunasor Sanim; Asep Saefuddin; Santun R.P. Sitorus (Faculty of Agriculture, Universitas Sebelas Maret, 2011)
Title : The Policy Direction for Controlling of Erosion and Sedimentation at Keduang Sub‐Watershed in Wonogiri Regency. Keduang Sub‐Watershed is one of important sub‐watershed at Bengawan Solo Watershed. Land resources management at Keduang Sub‐Watershed will be influence of environment quality, physic (erosion, sedimentation, debit of Keduang River), chemistry (water quality) and socio economic aspect. This aim research to know the level of erosion and sedimentation and to arrange policy direction for controlling erosion and sedimentation at Keduang Sub‐Watershed, Wonogiri Regency.Research method which is used is descriptive. Data types which are obtained are secondarydata from Centre of Research and Development Technology of Watershed Management, Forestry Department, BPS‐Statistic of Wonogiri Regency and Agriculture Department of Wonogiri Regency. Method of analysis’s data which is used in this research is Universal Soil Loss Equation (USLE) Method to predict the soil erosion. This research method also to arrange modelling of controlling erosion and sedimentation.Results of this research are: the level of erosion in Keduang Sub‐Watershed is 44 ton/ha/year or 1.9 million ton/year. The sediment yield from Keduang Sub‐Watershed to Wonogiri Basin equal 164,000 ton/year. Improving of construction terrace can reduce erosion and sedimentation.Keywords: land resources management, erosion, sedimentation, construction terrace